2013
DOI: 10.3109/13880209.2013.801994
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effect ofCetraria islandicaagainst diabetes-induced genetic and oxidative damage in human blood

Abstract: Context: The aqueous extracts of Cetraria islandica (L.) Ach. (Parmeliaceae) is traditionally used in many countries against a number of conditions, including inflammatory conditions. Objective: The present study aimed to assess, for the first time, the effectiveness of C. islandica in cultured primary blood cells of Type 1 diabetes subjects. Materials and methods: Diabetic and control blood samples were treated with or without aqueous lichen extract (5 and 10 mg mL À1) for 48 h. The activity of antioxidant en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
0
5
0
1
Order By: Relevance
“…Generally, antioxidant activity may be relevant as a mechanism for reversing cellular damage induced by metabolic dysfunction or by external factors. Radical scavenging capacity by several lichen extracts was reported recently, as well as in older work using extracts from cultured lichen material . Reports by Turkez and co‐workers suggest a protective role of lichen extracts against specific types of oxidative cell damage.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Generally, antioxidant activity may be relevant as a mechanism for reversing cellular damage induced by metabolic dysfunction or by external factors. Radical scavenging capacity by several lichen extracts was reported recently, as well as in older work using extracts from cultured lichen material . Reports by Turkez and co‐workers suggest a protective role of lichen extracts against specific types of oxidative cell damage.…”
Section: Introductionmentioning
confidence: 73%
“…Radical scavenging capacity by several lichen extracts was reported recently, 3,4 as well as in older work using extracts from cultured lichen material. 5 Reports by Turkez and co-workers 6 suggest a protective role of lichen extracts against specific types of oxidative cell damage.…”
Section: Introductionmentioning
confidence: 99%
“…One of the previous studies was stated that C.islandica could be a scavenger of superoxide radical (Gulcin et al, 2002) based on the ingredient of lichen and linoleic acid. Lichen has also prevented mutagenesis and carcinogenesis in human (Colak et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…So far, an enormous number of studies were conducted to identify novel, useful phototherapeutic agents including compounds derived from plants (Bontempo et al, 2015;Shweta, et al, 2013;Unnati Shah, 2013;Vaithiyanathan and Mirunalini, 2016), fungi (Shweta et al, 2013) and lichens (Kosanic, et al, 2013). It has suggested that lichens and their secondary metabolites can be used as an alternative method for the treatment of cancers (Kosanic et al, 2013(Kosanic et al, , 2014 due to its immune stimulation effect (Colak, et al, 2013). Recently, studies intended to show the effects of lichen extracts on various types of cancer are increasing (Coskun et al, 2015;Çelikler Kasımoğulları et al, 2014;He et al, 2010;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…В експерименті підтверджена антиоксидант на та антиканцерогенна дія цетрарії ісландської [19,22,24].…”
unclassified